Nitriding, oxidation and carburization of titanium and steels in non-self maintained gaseous discharge - Timoshenko, A.I.; Taran, V.S.; Misiruk, I.O. (Вопросы атомной науки и техники, 2012)
The samples of stainless steel (SS), high speed steel (HSS) and titanium (Ti) were exposed to fluxes of ions N⁺, O⁺, and CmHn⁺ which have been ejected from hollow anode into hollow cathode (vacuum chamber). It has been found that the oxidation of Ti is going faster than the nitriding does. The surface microhardness of samples treated by fluxes of ions in non-self maintained gaseous discharge grows from 1.5 for HSS (except the carburization) to 6 times for Ti and SS.